Structural behavior of reinforced concrete deep beams strengthened in flexure with CFRP - Raheem, Mustafa Mohammed (Kansas State University, 2019)
This research presents an analytical and experimental investigation for the use of flexural CFRP sheets as a strengthening technique to improve the shear capacity of reinforced concrete deep beams. The analytical work presents a new analysis method that is developed to predict the response of reinforced concrete deep beams with and without flexural CFRP strengthening. The method utilizes the truss analogy approach that is extended from the Strut-and-Tie Model (STM) for unstrengthened beams. In contrary to STM, the new method is used to capture the full structural response of unstrengthened beams by modeling a single truss. On the other hand, the new method is used to predict the entire response of strengthened beams by assuming the beam to be composed of two parallel compatible trusses. The first truss has its lower chord member composed of the steel bars while the second truss has its lower chord member composed of the flexural CFPR sheets. By imposing the compatibility condition of a statically indeterminate truss, the contribution of each truss is realized. The experimental work was conducted on three deep beam specimens with identical rectangular cross-sectional area. The first beam was tested as a control beam, and the other two beams were strengthened in flexure with four layers of flexural CFRP sheets anchored by two different flexural anchorage devices. The first strengthened beam was anchored with GFRP patches applied to both sides of the beam. The second strengthened beam was anchored with side GFRP bars inserted longitudinally to both sides of the beam. The comparison between the analytical and experimental results showed reasonable agreement and asserted the validity of the analytical approach and methodology developed in this study.
Keywords: Deep beam